Tabaquismo y su incidencia en el enfisema pulmonar en adultos mayores del recinto la revesa del cantón Babahoyo de la provincia los rios durante el primer semestre 2018 - Urrea Urrea, Norma María (2018)
Smoking is a damage of chronic features occurring in the person who consumes tobacco in excess. The concept is also used to appoint Addiction experienced by a subject by tobacco, which often generated by nicotine. Smoking has become a major health problem; this affects the respiratory tract due to its content it is highly toxic one of those it is nicotine that can cause increased blood pressure, heart rate also causes that the arteries to narrow. There have been cases of obstructive lung diseases such as emphysema, a condition that can be severe, especially children. In 2009, the rate of mortality due to emphysema was 21.8 per thousand older adults. In the results the implementation of surveys were fundamental since from here the most relevant data are obtained to answer our question of the problem, these surveys were applied in the location subject to study, and all the information that was extracted from the site are represented in each of the tables and graphs It is concluded that smoking affects the reverse in a predominant way on development of pulmonary emphysema in adults over the enclosure and that the social environment has much intervention in the manifestation of pulmonary emphysema.